LOAD STATIC SIMULATION OF TRANSMISSION ROD FOR DESIGN OF CHINESE SPINACH (IPOMOEA REPTANS POIR.) HARVESTER - Agustami Sitorus (Nusa Putra University, 2018)
The harvesting machine for Chinese spinach (Ipomoea reptans Poir.) has never been designed. In fact, appropriate technology is needed for Chinese spinach farmers in Indonesia. Therefore, this paper begins by designing the concept of Chinese spinach harvesters integrated with hand tractors. One of the most important parts of this integration process is the part of the transmission system that connects the power source to the harvesting unit. The proposed design concept is to use a rod transmission system. The transmission of the rod becomes crucial so it is important to perform dimensional analysis and determine its material type. Therefore, this study is to simulate the rod of the transmission system through load static simulations approach. Load static simulations run with the help of CAD applications. The material tested consisted of AISI 1010, AISI 1020, AISI 4340 with a material thickness of 2 mm, 4 mm and 5 mm respectively. The simulation results show that the AISI 1020 meter is better to use with a thickness of at least 2 mm. This result is also supported by an analysis using the laws of classical mechanics which state that the minimum thickness of the transmission rod is 0.6692 mm. The power to be transmitted to the harvesting machine is 1.3 hp.